Oxidative Stress-Related Gene Polymorphisms Are Associated With Hepatitis B Virus-Induced Liver Disease in the Northern Chinese Han Population - Ma, Ning; Liu, Wenxuan; Zhang, Xiaolin; Gao, Xia; Yu, Fengxue; Guo, Weiheng; Meng, Yanxin; Gao, Ping; Zhou, Jin; Yuan, Meina; Mi, Yingjun; Zhang, Lei; et al. (Frontiers in Genetics, 2020)
Background: Oxidative stress is closely related to the occurrence and development of various diseases such as cancer, diabetes, and cardiovascular and infectious diseases. We identified six critical genetic variants related to oxidative stress, and evaluated their main effects and their interaction effects on hepatitis B virus (HBV)-induced liver diseases. Methods: We enrolled 3128 Han Chinese subjects into five groups: healthy controls, chronic hepatitis B (CHB), liver cirrhosis (LC), hepatocellular carcinoma (HCC), and natural clearance. We then determined the genotypes in each group for CYBA-rs4673, NCF4-rs1883112, NOX4-rs1836882, rs3017887, SOD2-rs4880, and GCLM-rs41303970, and evaluated the association between these variants and HBV-induced liver diseases. Gene-gene interactions were evaluated using generalized multifactor dimensionality reduction, logistic regression, and four-by-two tables. Results: Significant associations were observed between healthy controls and the CIB group (CHB+LC+HCC). The CYBA-rs4673AG genotype was associated with a 1.356 rate of persistent HBV infection compared to the wild type GG genotype. The NCF4-rs1883112G allele occurred more frequently in healthy controls than in the CIB group in all three models (dominant, codominant, and recessive). Nox4-rs1836882 TC showed a protective association, being more frequent in healthy controls compared to the wild type TT genotype. GCLM-rs41303970A was associated with persistent HBV persistent infection. The overall best model by multifactor dimensionality reduction was a five factor interaction model that had the highest cross validation consistency (10/10) and test accuracy (0.5669), p = 0.001. Conclusions: Oxidative stress-related gene polymorphisms are likely to be associated with persistent HBV infection, suggesting that information on these variations is useful for risk assessment of HBV infection.